Prune Juice Containing Sorbitol, Pectin, and Polyphenol Ameliorates Subjective Complaints and Hard Feces While Normalizing Stool in Chronic Constipation: A Randomized Placebo-Controlled Trial - Koyama, Taishi; Nagata, Naoyoshi; Nishiura, Kengo; Miura, Naoki; Kawai, Takashi; Yamamoto, Hirotaka (The American journal of gastroenterology, 2022)
The aim of this study was to determine the effectiveness of prune juice on chronic constipation. We conducted a double-blind, randomized, placebo-controlled trial in Japanese subjects with chronic constipation. Prune intake significantly decreased hard and lumpy stools while increasing normal stool and not increasing loose and watery stools. Prune intake also ameliorated subjective complaints of constipation and hard stools, without alteration of flatulence, diarrhea, loose stools, or urgent need for defecation. There were no adverse events or laboratory abnormalities of liver or renal function after prune intake. Prune juice exerted an effective and safe natural food therapy for chronic constipation.